The strength of cytomorphology and efficacy of immuno‐cytochemistry in distinguishing hepatocellular carcinoma from its mimics on fine‐needle aspiration cytology. Issue 7 (30th April 2021) - Chikhale, Mangesh; Toi, Pampa Ch; Siddaraju, Neelaiah; Ananthakrishnan, Ramesh
Abstract: Background: Cytomorphologic distinction of hepatocellular carcinoma (HCC) from its mimics on fine‐needle aspiration cytology (FNAC) is often problematic. The present study evaluates the strength of cytomorphology and the utility of an immuno‐panel of arginase‐1, glypican‐3, HepPar‐1, thyroid transcription factor (TTF‐1) and CK‐19 in resolving this diagnostic issue. Methods: FNAC features of 71 nodular hepatic lesions were studied with an immunocyto/ histochemical (ICC/IHC) panel of arginase‐1, glypican‐3, HepPar‐1, TTF‐1 taking 10% positivity as "cut‐off." Cytomorpholologic diagnoses were compared with diagnoses made on combined cytomorphologic and ICC/IHC approach. Results: Of 71 cases, 32, 10 and 29 had histopathologic, cell block and clinico‐radiologic correlation respectively with 55 metastatic adenocarcinomas (MAC), 13 HCCs and one case each of hepatic adenoma (HA), cirrhotic nodule (CN) and intrahepatic cholangiocarcinoma (CC). Cytoplasmic positivity of HepPar‐1 and glypican‐3 were noted in 11/13 and 8/13 HCCs respectively; while only 3/13 and 1/13 HCCs revealed cytoplasmic positivity for arginase‐1 and TTF‐1 respectively. Benign hepatic lesions were negative for glypican‐3 and TTF‐1, but expressed both arginase‐1and HepPar‐1. Twenty‐one of 55 MACs and the lone case of CC were positive for CK‐19; however, all MACs and CC cases were negative for HepPar‐1, arginase‐1, glypican‐3 and TTF‐1. The immune‐panel had sensitivity, specificity and diagnostic accuracy of 100%, 88.9% and 90.6%, respectively, for differentiating HCC from its morphologic mimics. Conclusion: Though a meticulous cytologic evaluation in conjunction with clinicoradiologic profile helps in distinguishing HCC from its benign and malignant mimics; an immunopanel of arginase‐1, glypican‐3, HepPar‐1, TTF‐1 and CK‐19 drastically improves the diagnostic accuracy.